The NASA Wallops Flight Facility Digital Ozonesonde Record: Reprocessing, Uncertainties, and Dual Launches. Issue 6 (23rd March 2019) - Witte, Jacquelyn C.; Thompson, Anne M.; Schmidlin, F. J.; Northam, E. Thomas; Wolff, Katherine R.; Brothers, George B.
Abstract: The NASA Wallops Flight Facility (WFF; Wallops Is., VA, USA) is the longest continuously operating ozonesonde station in the continental United States (since 1970). The well‐established WFF ozonesonde system comprises a Science Pump Corporation (SPC) electrochemical concentration cell (ECC) ozone sensor with a 1% potassium iodide and phosphate buffer sensing solution type (SST), interfaced with a Lockheed Martin Sippican radiosonde that provides winds, GPS coordinates, pressure, temperature, and relative humidity. A major milestone has been achieved with the reprocessing of the WFF ozone profiles during the digital measurement era (since 1995) to remove known biases and improve overall accuracy. We present an overview of the reprocessing methods and evaluate the homogenized data set relative to the original records, colocated Dobson, and satellite overpasses. Reprocessing yields modest changes in total column ozone by up to 3%, affirming the high data quality of the original ozone records. First estimates of ozone uncertainty are summarized and found to be consistent with estimates from previous studies. WFF has a history of evaluating ozonesonde performance via dual sonde launches that have tested standard operating procedures and combinations of ECC sensors and SST formulae. This rich data set illustrates how various ECC/SST combinations affect the ozone measurement. Results from the dual launches reaffirm the World Meteorological Organization recommended standard operating procedures where the ozone agreement between the SPC/1% Buffer and EN‐SCI/0.5% Half Buffer pair is well within ±5% throughout the profile. Tests of the SST under field conditions reveal the high sensitivity of ozone measurements to the buffer strength. Key Points: This is the first reprocessing of the digital era ozonesonde records at NASA Wallops Flight Facility Modest changes after reprocessing affirm high data quality in original ozonesonde time series Ozone uncertainties fall below 8% and are ~5% throughout the middle stratosphere and lower troposphere, regardless of season